HUMAN CAPITAL DEVELOPMENT IN IRAQ: ANALYZING REALITY AND CHALLENGES IN THE CONTEXT OF ECONOMIC TRANSFORMATIONS - Assist. Prof. Dr. Shaymaa Rasheed Mohaisen (Scholar Express Journals, 2025)
Human capital is a pivotal element in promoting sustainable economic and social development, given its vital role in raising productivity rates, stimulating innovation, and achieving sustainable growth. This research aims to provide a comprehensive analysis of the reality of human capital development in Iraq, focusing on current challenges in light of rapid economic transformations, whether these transformations result from changes in economic policies or are influenced by successive security and financial crises. The research relied on a descriptive analytical approach, reinforced by analyzing data from reliable sources, in addition to the results of a questionnaire directed at a sample of workers in the educational and economic sectors. The research examined the main indicators of human capital: education, health, and skills development, while analyzing the impact of economic variables on these indicators for the period (2010-2024).
Keywords: human capital; economic transformations; abor market